Transformasi Pengelolaan Hutan Lindung ke Lahan Pertanian di Lombok Timur Perspektif Fikih Al-Bi’ah - Muh. Rizal Hamdi (Jurnal Hukum Lex Generalis, 2026)
This study examines the transformation of protected forest management into agricultural land in the Sekaroh area, Jerowaru Subdistrict, East Lombok Regency, from the perspective of fiqh al-bi’ah. There are three questions to be addressed: what are the ecological impacts resulting from the conversion of the protected forest; Second, what is the legal framework and third, how does the fiqh al-bi’ah perspective view this phenomenon. This study employs a descriptiveanalytical paradigm with a qualitative research design and utilizes a normative sociological approach. Data collection techniques include observation, interviews and documentation. To validate the data, the researcher employed triangulation, extended fieldwork and discussions. The results of this study indicate that the conversion of protected forest land into agricultural land for corn cultivation in the Sekaroh Forest Area is unavoidable to meet the economic needs of the surrounding community. However, the conversion of protected forest into agricultural land, without sound environmental planning, is not justified under the principles of fiqh al-bi’ah because it disrupts ecological balance and disregards the public interest.